Music elicits different gene expression responses in the buccal cavity of age-related cognitive disorders patients and healthy controls - Gómez-Carballa, Alberto; Navarro, Laura; Mallah, Nour El Zahraa; Bello, Xabier; Pischedda, Sara; Viz-Lasheras, Sandra; Currás, María José; Ferreirós-Vidal, Isabel; Mallah, Narmeen; Montoto-Louzao, Julián; Camino-Mera, Alba; Castelo-Martínez, Lúa; et al. (Frontiers in Aging Neuroscience, 2025)
IntroductionRecent evidence suggests that external stimuli can shape transcriptomes, a field emerging as sensogenomics. Specifically, the analysis of capillary blood samples has shown that musical stimuli can modulate gene expression patterns, not only in healthy individuals but also in those with age-related cognitive disorders (ACD).MethodsUsing targeted transcriptomics with Nanostring nCounter, we present groundbreaking evidence indicating that brief exposure to music can also impact the buccal transcriptome in both healthy donors and ACD patients.ResultsOur findings reveal that music elicits stronger transcriptomic effect on patients compared to controls, driving global upregulation in ACD patients but downregulation in controls. The most significantly dysregulated genes in ACD patients include LGALS3 (downregulated) and CXCL8 (upregulated), whereas in controls, THOP1 was the top significant gene (downregulated). These genes play important roles in normal brain functions and are also altered in neurodegenerative conditions. Weighted Gene Co-expression network analysis reveals relevant and significant modules, both positive and negative correlated with music, implicated in neurodegenerative (e.g., autophagy) and immunological processes (e.g., IL-1, MHC).DiscussionCollectively, these results suggest a complex interplay between music and molecular responses in the human body, and highlight the potential of musical stimuli to influence gene expression patterns outside systemic circulation, paving the way for further exploration of music’s therapeutic applications.